Buenas prácticas agrícolas en los cultivos de maíz (Zea mays L.) Y ARROZ (Oryza sativa L.) Parroquia San Plácido, Cantón Portoviejo. - Navarrete Ormaza, Byron Enrique (2012)
This study was conducted in the winter of 2010, between the months of January to June, on sites Las Losas, Rio Chico and El Progreso belonging to San Plácido, Portoviejo , with the purpose of demonstrating the "Good agricultural practices in corn (Zea mays L.) and rice (Oryza sativa L.) San Plácido, Portoviejo". We implemented half-tech plots and plots producer to demonstrate the impact of good agricultural practices (GAP) in maize and rice. We used the method of paired comparisons. The variables evaluated were corn plant height at 30 and 45 days after planting (DAP) in centimeter (cm), stem diameter at 50 DDS, cob diameter, cob length, number kernels per cob, cob weight, cob average weight and maize yield in quintals per hectare, and on rice were: plant height at 40 DDS in cm, number of panicles, number of grains per spike, grain length, paddy rice yield and milled rice yield per plant and hectare. Regarding the production variables evaluated, the differences mainly reflect the plots semi-technologically advanced, excelling the site "El Progreso" which had the highest average yield of 186.48 bushels corn per hectare (q / ha) and in milled rice yield with 48.40 quintals / ha.